Sweetshop of dreams eaudiobook - Colgan, Jenny (Rosie Hopkins, 2018)
Rosie Hopkins thinks leaving her busy London life, and her boyfriend Gerard, to sort out her elderly Aunt Lilian's sweetshop in a small country village is going to be dull. Boy, is she wrong. Rosie's life is . . . comfortable. And even though she might like to pursue a more rewarding career, and Gerard doesn't seem to have any plans to propose, Rosie's not complaining. Things could be worse. Right? Lilian Hopkins has spent her life running Lipton's sweetshop, through wartime and family feuds. When her great-niece Rosie arrives to help her with the shop, Lilian struggles with the idea that it might finally be time to settle up, and wrestles with the secret history hidden behind the jars of beautifully colored sweets. But as Rosie gets Lilian back on her feet, breathes a new life into the candy shop, and gets to know the mysterious and solitary Stephen—whose family seems to own the entire town—she starts to think that settling for what's comfortable might not be so great after all.